+0  
 
+1
149
2
avatar

What is 6(x-6)-5(x-7)=x+6?

Guest Mar 20, 2017
Sort: 

2+0 Answers

 #1
avatar+10614 
+1

First step...use distributive propety to expand to:

6x - 36 - 5x + 35 = x+6     gather like terms

x - 1 = x + 6        Uh - Oh      there is no solution to this !

ElectricPavlov  Mar 20, 2017
 #2
avatar+6810 
0

6(x-6)-5(x-7)=x+6

6x-36-5x+35 = x+6

x - 1 = x + 6 WHAT!????

MaxWong  Mar 23, 2017

23 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details